Effects of compounds on C. elegans DMD model health - Ellwood, Rebecca A. (2022)
Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder caused by mutations in the dystrophin gene. The dystrophin gene encodes a cytoskeletal protein with the same name that is responsible for ensuring the strength, stability, and functionality of myofibers. In DMD the dystrophin protein is either absent or there are insufficient levels of functional dystrophin resulting in progressive muscular damage and degeneration. This results in muscular weakness, motor delays, loss of ambulation, and a shortened life expectancy due to respiratory impairment and cardiomyopathy. Treatment options are limited and mainly focused on alleviating symptoms; they are not a cure. The main therapeutic treatment used are glucocorticoids, these can be used for a couple of years, but treatment is often ceased due to undesirable side effects. An emerging therapy is the use of exon-skipping but currently these can only be used for patients amenable to skipping of exons 45, 51, and 53 (approximately 30% of patients). There is therefore a great need for alternative therapies.